A Direct Interaction with RNA Dramatically Enhances the Catalytic Activity of the HIV-1 Protease In Vitro. Issue 14 (17th July 2015) - Potempa, Marc; Nalivaika, Ellen; Ragland, Debra; Lee, Sook-Kyung; Schiffer, Celia A.; Swanstrom, Ronald
Abstract Though the steps of human immunodeficiency virus type 1 (HIV-1) virion maturation are well documented, the mechanisms regulating the proteolysis of the Gag and Gag-Pro-Pol polyproteins by the HIV-1 protease (PR) remain obscure. One proposed mechanism argues that the maturation intermediate p15NC must interact with RNA for efficient cleavage by the PR. We investigated this phenomenon and found that processing of multiple substrates by the HIV-1 PR was enhanced in the presence of RNA. The acceleration of proteolysis occurred independently from the substrate's ability to interact with nucleic acid, indicating that a direct interaction between substrate and RNA is not necessary for enhancement. Gel-shift assays demonstrated the HIV-1 PR is capable of interacting with nucleic acids, suggesting that RNA accelerates processing reactions by interacting with the PR rather than the substrate. All HIV-1 PRs examined have this ability; however, the HIV-2 PR does not interact with RNA and does not exhibit enhanced catalytic activity in the presence of RNA. No specific sequence or structure was required in the RNA for a productive interaction with the HIV-1 PR, which appears to be principally, though not exclusively, driven by electrostatic forces. For a peptide substrate, RNA increased the kinetic efficiency of the HIV-1 PR by an order of magnitude, affecting both turnover rate (kcat) and substrate affinity (Km). These results suggest that an allosteric binding site exists on the HIV-1 PR and that HIV-1 PR activity during maturation could be regulated in part by the juxtaposition of the enzyme with virion-packaged RNA.